PENGARUH RASIO MOLAR MINYAK JELANTAH DENGAN METANOL DAN SUHU REAKSI DALAM REAKSI TRANSESTERFKASI TERKATALIS CaO/ZEOLIT ALAM TERHADAP YIELD BIODIESEL - Malia, Ana; Suarya, Putu; Raka Astiti Asih, Ida Ayu; Wisnu Adhi Putra, I Made (Jurnal Kimia (Journal of Chemistry); Vol. 10, No. 1 Januari 2016DO - 10.24843/JCHEM.2016.v10.i01.p07, 2016)
The research of transesterification reaction catalyzed by CaO/natural zeolite has been carried out. This work was aimed to obtain the high yield of biodiesel. The supporting process of CaO on natural zeolite (CaO/ZAA) was done by using wet impregnation method and characterization of CaO/ZAA was performed using XRD, FTIR and the determination of specific surface area of natural zeolite as CaO supporter was performed by BET method. This research aims to study the influence of transesterification reaction which was executed by varying molar ratio of oil to methanol and reaction temperature. Analysis of functional groups and minerals using FTIR and XRD, respectively, showed no significant changes before and after the impregnation of CaO on natural zeolites. CaO supported on natural zeolite was undetected by FTIR. Instead, it was detected by the vibration of carbonate groups as the result of the CO 2 absorption by CaO and the result of surface area analysis using BET method showed that the greater the size of natural zeolite, the smaller the specific surface area of catalyst. The result analysis using BET method showed that the spesific surface area of 200 mesh sized natural zeolite as CaO supporter was 9.993 m 2 /g. The simple gravimetric test revealed that  the amount of CaO supported on 200 mesh sized natural zeolite was 0.2155 g/g. It was concluded that CaO/ZAA 200 mesh was the most suitable catalyst which was then used in the production of biodiesel. The transesterification result showed that the highest biodiesel yield of 98.34% was gained at molar ratio of oil to methanol of 1:15 and at the temperature of 60 o C. The GC-MS analysis indicated that the main components of the biodiesel were methyl palmitate and methyl oleate.
Keywords: CaO catalyst, natural zeolite, transesterification, biodiesel